2021
DOI: 10.3389/fvets.2021.650291
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Safety, Immunogenicity, and Reproductive Effects of Combined Vaccination With Anti-GnRH (Gonacon) and Rabies Vaccines in Female Feral Cats

Abstract: Overpopulation of free-roaming cats is a major problem leading to negative impacts on animal health and welfare, public nuisance, transmission of zoonotic diseases, and well-documented harm to wildlife. Surgical sterilization had failed to provide a practical solution to free-roaming cats' overpopulation under field conditions; therefore, efficient and safe non-surgical immunocontraception methods are aspired. Rabies is a deadly virus that may infect people and animals. However, the safety and efficacy of comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…Behavioural conditions have multiple causes, and they are rarely, if ever, caused by gonadectomy only. The decision by owners to gonadectomise male dogs in particular is strongly influenced by the erroneous perceived expectation of improvement or prevention of unwanted aggression (offending biting towards dogs and defensive bites towards humans) after surgery (Da Costa et al, 2022;Downes et al, 2015;Notari et al, 2020). Also, despite evidence to the contrary, there is a commonly held erroneous notion that there is a consistent association between levels of serum testosterone concentrations and aggressive behaviour of all types in dogs (Garde et al, 2016).…”
Section: Behavioural Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural conditions have multiple causes, and they are rarely, if ever, caused by gonadectomy only. The decision by owners to gonadectomise male dogs in particular is strongly influenced by the erroneous perceived expectation of improvement or prevention of unwanted aggression (offending biting towards dogs and defensive bites towards humans) after surgery (Da Costa et al, 2022;Downes et al, 2015;Notari et al, 2020). Also, despite evidence to the contrary, there is a commonly held erroneous notion that there is a consistent association between levels of serum testosterone concentrations and aggressive behaviour of all types in dogs (Garde et al, 2016).…”
Section: Behavioural Concernsmentioning
confidence: 99%
“…All female cats vaccinated with a GnRH vaccine in combination with a rabies vaccine (n=5) had a significant reduction in anti‐Müllerian hormone serum concentrations and evaluation of vaginal cytology and ovarian histology suggested that reproductive cyclicity was suppressed (Novak et al., 2021). Female cats immunised with a GnRH vaccine (n=15; 0.5 mL IM once) were introduced to fertile male cats 4 months after vaccination (Levy et al., 2011).…”
Section: Non‐surgical Sterilisation In Dogs and Catsmentioning
confidence: 99%
“…However, community cats may be at risk of contracting the disease if they come into contact with infected animals and are not vaccinated. Hence, it is crucial to implement community cat management programs in developed countries that include rabies vaccination for these animals [43,44].…”
Section: Public Health Effects: Reality Vs Perceptionmentioning
confidence: 99%
“…Como efectos colaterales pudieron advertir la formación de masas en el lugar de la aplicación; no obstante, estas no fueron dolorosas ni ocasionaron dificultad para deambular. Además, la administración de GonaCon™ junto con la vacuna antirrábica resulta efectiva y segura a corto plazo (Novak et al, 2021).…”
Section: Vacunas Anti-gnrhunclassified